Inside ownership beyond the IPO: the evolution of corporate ownership concentration - Harjoto, Maretno; Garen, John (Journal of Corporate Finance, 2005)
This study examines the firm's equity ownership by insiders and blockholders starting right after the firm goes public, its decline thereafter, and what alters the decline. Previous literature has shown the incentive of insiders to let their ownership fall after their initial public offering (IPO). After the IPO, management attains only a fraction of the benefits of good governance, so has an incentive to let inside ownership erode. We verify this, but examine the effect that re-entry into capital market via a seasoned equity offering (SEO) has on insider ownership. The incentive of management to hold stock is restored by a desire to raise additional capital because it implicitly raises management's stake. We show empirically that it raises insider stockholding relative to what it otherwise would have been, thus providing an avenue by which this aspect of corporate governance is improved. This, and other results, is shown with a sample of IPO firms during 1996 and 1997. Our findings indicate that, in expectation, the increased holdings due to re-entry into the capital market almost exactly offsets 1 year's downward trend in management shareholdings. Also, we find an interesting interplay between types of blockholders in that CEOs tend to hold less stock after the IPO if external blockholders initially hold more.